Agronomic methods for Striga (Striga asiatica) control in dryland maize in Limpopo Province - Mathobo, Rhudzani (My University, 2008)
Striga control through agronomic practices is the key to maize production predominantly in small holder farmers who cannot afford chemical weed control. Striga has affected maize yield in many areas in Limpopo Province, South Africa. Field experiments were carried out over one season at three sites to determine the effect of weed control method on striga on maize. The experiment was done at Mafarana village (Mopani District) near Tzaneen where striga is a serious problem. It was conducted on three fields, belonging to Mrs. Shingwenyana, Mr. Nyathi and Mr. Mushwana. A randomized complete block design experiment was laid out consisting of two factors; (i) two maize cultivars i.e. Zm 1421 and Zm 423 (ii) three agronomic practices: hand hoeing alone (as the control factor), hand hoeing plus inorganic fertilization using lime ammonium nitrate (LAN-28%N) at the rate of 56kg/ha, and hand hoeing plus inter-row intercropping of maize with cowpea. Cowpea cultivar Bechuana White was used for the experiment. The results indicated that the effect of the method of weed control on the number of striga plants was significant at the 5% level of significance at all locations except at Mushwana’s where at 105 days after planting (DAP) there was no significant effect. Striga numbers were lower in hand hoed plus inorganic fertilizer plots compared to hand hoed alone and hand hoed plus intercropping. At Shingwenyana’s field the results indicated that effect of weed control methods on grain yield was significant and this is where the striga numbers were the highest than at Mushwana and Nyathi’s fields. The effect of weed control methods on grain yield was significant only at Shingwenyana’s field ranging from 2219kg/ha (hand hoeing), 2248kg/ha (hand hoeing plus inorganic fertilizer) to 3928kg/ha (hand hoeing plus intercropping). The effect of weed control method on shelling %, hundred seed weight, number of cobs per plant and lodging % was not significant. The effect of weed control method on number of plants per plot was significant at Mushwana’s field only. There was significant difference of striga numbers among maize varieties at Nyathi’s field at 105 DAP. In hand hoed, striga numbers were 0.075 for Zm 1421 and 0.489 for Zm 423. Plots that were hand hoed plus inorganic fertilizer application striga numbers were 0.075 for Zm 1421 and 0.270 for Zm 423 and finally hand hoed plus intercropped plots with maize and cowpeas had striga numbers of 0.739 for 1421 and 0.850 for ZM 423. It is recommended that farmers improve the fertility status of their soils in order to control striga problem.
Thesis (M. Sc. Agriculture (Crop Science)) -- University of Limpopo, 2008
Keywords: Weed control